PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF COGNITIVE INTERESTS IN PRIMARY SCHOOL STUDENTS - Kilichenko, Oksana; Komar, Olha (Mountain School of Ukrainian Carpaty, 2022)
The article examines pedagogical conditions for the development of cognitive interests in children of primary school age. It is noted that a modern school, which activities take place in difficult conditions: the war with Russia, the Covid pandemic, is focused not only on the transfer of knowledge, but on the formation of competencies. Effective educational activity is impossible without the development of stable cognitive interests in students. The concept of "interest" is concretized, the concept of "cognitive interest" is considered, and the pedagogical conditions for its development in elementary school students are determined. Among the main conditions we highlight the following: the student's understanding and awareness of the content and meaning of the studied material, and not only the perceived educational information, the development of critical thinking. Use of the new in the content of the subject. Adhere to the principle of anticipatory learning, which contributes not only to the gradual assimilation of educational material by all students, but also develops inquisitiveness, immersion in knowledge. The formation of cognitive interests of primary school students depends on the emotional appeal of learning and is closely related to the development of emotional intelligence, as the ability of an individual to recognize his own and other people's emotions, desires, attitude to learning, intentions and manage them. In addition to traditional methods of organizing the educational process in primary school, the formation of cognitive interests is influenced by the use of problem-based, interactive, integrated learning. An important condition for the formation of the cognitive interest of primary school students in the learning process is the use of game technologies. In modern conditions the implementation of information and communication technologies in primary school lessons is of particular importance. The use of an optimal system of creative training exercises and cognitive tasks in the educational process in accordance with the content of the educational material, features and capabilities of students plays a special role in the process of developing cognitive interests in primary school students.